RELATIONAL CAPITAL DI UTU - Dara Angreka Soufyan; Yoga Nugroho (Jurnal Manajemen Inovasi, 2018)
One of the important things in managing the university is Relational capital (RC). That is the relationship between human capital and stakeholders. This study aims to identify intangible assets classified as RC components at UTU in 2017. Using qualitative methods and using 16 elements of replication of Ramirez and Gordillo's research, the result showed that elements of social responsibility are not identified in UTU. Meanwhile, 15 other elements were identified from amount of 16 RC elements used. RC elements that are perfectly identified are the relationships that UTU has with prestigious and quality institutions and social and cultural commitments.Key wordsRelational Capital, Intangible Assets, Intellectual Capital, University, UTU